2022
DOI: 10.7554/elife.78330
|View full text |Cite
|
Sign up to set email alerts
|

Microtubules restrict F-actin polymerization to the immune synapse via GEF-H1 to maintain polarity in lymphocytes

Abstract: Immune synapse formation is a key step for lymphocyte activation. In B lymphocytes, the immune synapse controls the production of high-affinity antibodies, thereby defining the efficiency of humoral immune responses. While the key roles played by both the actin and microtubule cytoskeletons in the formation and function of the immune synapse have become increasingly clear, how the different events involved in synapse formation are coordinated in space and time by actin-microtubule interactions is not understoo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 62 publications
5
6
0
Order By: Relevance
“…They also suggested the inhibitory effect of microtubules on actin network remodeling and membrane ruffling. A similar regulatory effect of microtubules has been reported by Pineau et al (2022) [ 33 ]. They demonstrated that microtubules and the GEF–H1–RhoA axis had an inhibitory effect on actin polymerization at the lymphocyte–antigen contact site.…”
Section: Discussionsupporting
confidence: 86%
“…They also suggested the inhibitory effect of microtubules on actin network remodeling and membrane ruffling. A similar regulatory effect of microtubules has been reported by Pineau et al (2022) [ 33 ]. They demonstrated that microtubules and the GEF–H1–RhoA axis had an inhibitory effect on actin polymerization at the lymphocyte–antigen contact site.…”
Section: Discussionsupporting
confidence: 86%
“…In the course of optimizing the classification, an additional phenotype termed “patchy” was discovered. A similar distribution of multiple F‐actin polymerization spots was described at the cortex of T cells during immune synapse formation upon microtubule depolymerization 18 . The patchy fraction was affected by treatments with CS and NSC, indicating that it constitutes a bona fide biological phenotype to be further investigated.…”
Section: Discussionsupporting
confidence: 55%
“…In our experiments, LatA did not induce the formation of the static protrusive structure when the microtubule cytoskeleton was depolymerized priorly, an observation in line with Obino et al ( 2016 ). Microtubule‐mediated polarity cues for protrusion formation could involve regulating the phosphoinositide content of the plasma membrane (Golub & Caroni, 2005 ; Sugiyama et al , 2015 ), asymmetrically activating Rho signaling (Pineau et al , 2022 ) or providing direct interaction with membrane‐bending factors (Kelley et al , 2015 ). We think that, once these factors, likely to belong to the BAR protein superfamily, stably bind and bend membranes in the absence of actin cytoskeleton, subsequent microtubule depolymerization is no longer effective.…”
Section: Discussionmentioning
confidence: 99%